Associations of hiatus hernia with CT-based interstitial lung changes: the MESA Lung Study. Issue 1 (26th January 2023) - Kim, John S.; Kim, Jinhye; Yin, Xiaorui; Hiura, Grant T.; Anderson, Michaela R.; Hoffman, Eric A.; Raghu, Ganesh; Noth, Imre; Manichaikul, Ani; Rich, Stephen S.; Smith, Benjamin M.; Podolanczuk, Anna J.; et al.
Background: Hiatus hernia (HH) is prevalent in adults with pulmonary fibrosis. We hypothesised that HH would be associated with markers of lung inflammation and fibrosis among community-dwelling adults and stronger among MUC5B (rs35705950) risk allele carriers. Methods: In the Multi-Ethnic Study of Atherosclerosis, HH was assessed from cardiac and full-lung computed tomography (CT) scans performed at Exam 1 (2000–2002, n=3342) and Exam 5 (2010–2012, n=3091), respectively. Percentage of high attenuation areas (HAAs; percentage of voxels with attenuation between −600 and −250 HU) was measured from cardiac and lung scans. Interstitial lung abnormalities (ILAs) were examined from Exam 5 scans (n=2380). Regression models were used to examine the associations of HH with HAAs, ILAs and serum matrix metalloproteinase-7 (MMP-7), and adjusted for age, sex, race/ethnicity, educational attainment, smoking, height, weight and scanner parameters for HAA analysis. Results: HH detected from Exam 5 scans was associated with a mean percentage difference in HAAs of 2.23% (95% CI 0.57–3.93%) and an increase of 0.48% (95% CI 0.07–0.89%) per year, particularly in MUC5B risk allele carriers (p-value for interaction=0.02). HH was associated with ILAs among those <80 years of age (OR for ILAs 1.78, 95% CI 1.14–2.80) and higher serum MMP-7 level among smokers (p-value for smoking interaction=0.04). Conclusions: HH was associated with more HAAs over time, particularly among MUC5B risk allele carriers, and ILAs in younger adults, and may be a risk factor in the early stages of interstitial lung disease. In a population cohort, hiatus hernia detected by computed tomography (CT) was associated with increased lung densities on CT over time, especially among carriers of the MUC5B (rs35705950) risk allele, and may be a risk factor in interstitial lung disease https://bit.ly/3xakyeW